2D Mapping and boundary detection using 2D LIDAR sensor for prototyping Autonomous PETIS (Programable Vehicle with Integrated Sensor) - Hanugra Aulia Sidharta; Sidharta Sidharta; Wina Permana Sari (Universitas Muhammadiyah Malang, 2019)
PETIS (Programable Vehicle with Integrated Sensor) is a research project with goal make a robot that move independently with specific purpose. Due complexity of PETIS, research divide into several important sequence. In this research author focus on sense of sight for PETIS, LIDAR chosen due flexible and comprehensive. There is many LIDAR sensor in marketplace, LDS-01 as one of commercial LIDAR sensor available on market, produced by ROBOTIS as one of low-cost LIDAR sensor. Compare with another sensor that cost more than 1000, LDS-01 just cost lower than 500. On this research study focus with LDS-01 sensor reading, include hardware, software connection, and data handling. Based on this research LDS-01 as LIDAR sensor can read obstacle with minimum 29,9 cm and maximal 290,7 cm. Comparing with datasheet LDS-01 should work from 12 cm through 350 cm.